BIOGRAFI INTELEKTUAL PROF.DR. I GDE PARIMARTHA M.A. (1943-2014) - Putu Wiyoga, Ida Bagus (Humanis; Volume 15. No.3. Juni 2016, 2016)
Prof. Dr. I Gde Parimartha M.A. is a professor of History of Science at the Faculty of Literature and Humanities University of Udayana. Parimartha was born in the village of Tenganan DauhTukad December 31, 1943. Coming from a family background of farmers Parimartha through life simply. Starting from the motivation to move forward he tried to change the fate of the consistent continuing education in the academic field. Successfully completed education up to college level, Parimartha chose to serve and dedicate themselves academically to become a lecturer at the History of Science Program Faculty of Letters Udayana University. Parimartha for the devotion and dedication as a lecturer in the field of History from 1976, In 2003 Parimartha finally confirmed as Professor of the History of Science at the University of Udayana.
Keywords: Farmers, Motivation, Professor